Aplicação de reguladores vegetais na produção e qualidade de frutos do tomateiro - Weber, Ronald Ernst Heinrich [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present study was carried out to evaluate the answers of the foliar application of different rates of commercial mixtures of plant growth regulators (PGR) on the development of tomato fruits, aiming the evaluation of production of fruits and quality of the pulp. The tested mixtures were combined of citokinin (CK) and giberelic acid (GA) and of auxin (AX), citokinin (CK) and giberelic acid (GA). Two different trials were installed with randomized blocks, consisting of six treatments and of five replications, evaluating the production of the initial trusses of tomato fruits. The treatments were untreated check (UTC), GA4+7 + 6-BA at 60 mL ha-1, 120 mL ha-1 and 180 mL ha-1 and the mixture IBA + GA3 + Kt at rates of 500 mL ha-1 and 750 mL ha-1. Four applications were sprayed on each trial, starting with the first application when 50% of the flowers of the first truss were blooming. Intervals of 15 days were observed between the applications. The Experiment 1, located in Engenheiro Coelho - SP, used hybrid 'Paronset', from the Salada group, planted in open field. The results, considering number of fruits and production of the sum of all four evaluated trusses, did not differ statistically between the treatments, but all treatments with PGR's showed lower number of fruits than the UTC, with the mixture GA4+7 + 6-BA,at the rate of 120 mL ha-1, showing the reduction of 8,3% or 55 fruits compared with 60 fruits from UTC. The mixture IBA + GA3 + Kt at the lower rate (500 mL ha-1) improved fresh and dry mass in relation to the UTC by 4,4 and 4,7% respectively. The mixture GA4+7 + 6-BA produced lower fresh and dry mass. None of the PGR treatments resulted in changes in the internal quality of the fruits. On Experiment 2, located in Salto, using hybrid 'Myla', from the Cherry group, planted in protected ...

O trabalho objetivou avaliar as respostas da aplicação foliar de diferentes dosagens de misturas comerciais de reguladores vegetais no desenvolvimento de frutos de tomateiro, buscando analisar o aumento da produção e qualidade de frutos. Foram testadas a mistura de citocinina (CK) e giberelinas (GA) e a combinação de auxina (Ax), citocinina (CK) e giberelina (GA). Dois experimentos foram conduzidos em blocos ao acaso, consistindo de seis tratamentos com cinco repetições e avaliando a produção dos primeiros cachos. Os tratamentos foram: Testemunha; mistura de ácido giberélico (GA4+7) + 6-benziladenina (6- BA) a 60 mL ha-1, 120 mL ha-1 e 180 mL ha-1 e a mistura de ácido indolilbutírico (IBA) + ácido giberélico (GA3) + cinetina (Kt) nas dosagens de 500 mL ha-1 e 750 mL ha-1. Foram realizadas quatro aplicações com a primeira aplicação realizada na antese do primeiro cacho floral - com 50% das flores abertas, seguindo posteriormente com intervalos de 15 dias. No Experimento 1, localizado no município de Engenheiro Coelho (SP), usou-se o híbrido 'Paronset', do grupo Salada, plantado em campo aberto. Os resultados, considerando-se todos os frutos dos primeiros quatro cachos que foram avaliados, não diferiram estatisticamente entre os tratamentos e todos os tratamentos de misturas de reguladores vegetais apresentaram porcentagem inferior de número de frutos em relação à testemunha, sendo a mistura GA4+7 + 6-BA na dosagem de 120 mL ha-1 menor em 8,3% com a média de 55 frutos em relação à testemunha que produziu 60 frutos. A mistura de IBA + GA3 + Kt na dose menor (500 mL ha-1) apresentou massa fresca e massa seca superior em relação a testemunha em 4,4 e 4,7%, respectivamente. O tratamento da mistura de GA4+7 + 6-BA mostrou redução de massa fresca e massa seca. Nenhum tratamento de reguladores vegetais apresentou alterações qualitativas em relação à testemunha. ...
Application of plant growth regulators on the production and quality of tomato fruits
Keywords: Citocinas; Auxina; Giberelina; Tomate - Cultivo; Produtividade agrícola; Polpa de frutas - Qualidade; Tomatoes